2017
DOI: 10.1111/nph.14420
|View full text |Cite
|
Sign up to set email alerts
|

Loss‐of‐function mutation of the calcium sensor CBL1 increases aluminum sensitivity in Arabidopsis

Abstract: Despite the physiological importance of aluminum (Al) phytotoxicity for plants, it remained unknown if, and how, calcineurin B-like calcium sensors (CBLs) and CBL-interacting protein kinases (CIPKs) are involved in Al resistance. We performed a comparative physiological and whole transcriptome investigation of an Arabidopsis CBL1 mutant (cbl1) and the wild-type (WT). cbl1 plants exudated less Al-chelating malate, accumulated more Al, and displayed a severe root growth reduction in response to Al. Genes involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 94 publications
(132 reference statements)
1
36
0
Order By: Relevance
“…In the case of molecular processes activated in the Aluminum response gene set ( Figure 4A ), we found that the transcript levels of several proteins with kinase activity are increased by Al stress. The upregulation of genes that code for kinases agrees with previous works reporting the involvement of protein phosphorylation in the response of plants to Al 3+ stress ( Osawa and Matsumoto, 2001 ; Panda and Achary, 2014 ; Ligaba-Osena et al., 2017 ). Among the multiple genes coding for kinases enriched in the Aluminum response we found PROLINE RICH LIKE EXTENSION KINASE 4 ( PERK4 ) whose mutant, perk4 , has reduced sensitivity to abscisic acid (ABA) including reduced inhibition of root growth in response to ABA treatment ( Bai et al., 2009 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the case of molecular processes activated in the Aluminum response gene set ( Figure 4A ), we found that the transcript levels of several proteins with kinase activity are increased by Al stress. The upregulation of genes that code for kinases agrees with previous works reporting the involvement of protein phosphorylation in the response of plants to Al 3+ stress ( Osawa and Matsumoto, 2001 ; Panda and Achary, 2014 ; Ligaba-Osena et al., 2017 ). Among the multiple genes coding for kinases enriched in the Aluminum response we found PROLINE RICH LIKE EXTENSION KINASE 4 ( PERK4 ) whose mutant, perk4 , has reduced sensitivity to abscisic acid (ABA) including reduced inhibition of root growth in response to ABA treatment ( Bai et al., 2009 ).…”
Section: Resultssupporting
confidence: 91%
“…CIPK17 has been reported to participate in a signaling module that controls Ca 2+ influx and regulates ABA-signaling during stomatal closure ( Song et al., 2018 ). Moreover, the expression of CALCINEURIN B-LIKE PROTEIN 1 (CBL1) was also induced in response to Al, cbl1 mutants have increased sensitivity to Al 3+ toxicity and have downregulated expression of CIPK17 ( Ligaba-Osena et al., 2017 ). CBL1-CIPK17 have been reported to interact in vivo ( Kolukisaoglu et al., 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…The earliest studies on AtCBL1 indicated that it was a multifunctional and important protein. Subsequently, numerous studies have confirmed this hypothesis [97,[125][126][127]. We introduce them in the corresponding section.…”
Section: Functions Of the Cbl-cipk Pathwaymentioning
confidence: 86%
“…In Arabidopsis , 10 genes ( CBL1-10 ) encoding CBL proteins have been found ( Kolukisaoglu et al, 2004 ). CBL1 and CBL9 were reported to positively regulate the uptake and transport of K + , NO 3 − , NH 4 + , aluminum and iron, and the promotion of stomatal opening ( Li et al, 2006 ; Xu et al, 2006 ; Ho et al, 2009 ; Mao et al, 2016 ; Tian et al, 2016 ; Ligaba-Osena et al, 2017 ; Straub, Ludewig & Neuhäuser, 2017 ). CBL1 and CBL9 also affect abscisic acid (ABA)-induced stomatal closure and ROS signaling ( Pandey et al, 2004 ; Cheong et al, 2007 ; Drerup et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%